2016
DOI: 10.15836/ccar2016.307
|View full text |Cite
|
Sign up to set email alerts
|

Acute Coronary Syndrome in Croatia.

Abstract: SAŽETAK: Hrvatska u području liječenja akutnoga koronarnog sindroma metodama intervencijske kardiologije (perkutane koronarne intervencije, PCI) vrlo usko prati svjetske rezultate unatoč relativno niskim ulaganjima u zdravstveni sustav u usporedbi s razvijenim zemljama. U posljednjih desetak godina, otkada postoji Hrvatska mreža primarne PCI, hitno je liječeno nešto više od 15 000 bolesnika s akutnim infarktom miokarda s elevacijom ST segmenta (STEMI), a, prema istom principu, liječe se i drugi bolesnici s nes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…According to this and other investigations 15 , there is a respectable access to tertiary hospitals for urgent cardiac patients in Croatia. tertiary hospitals are distributed across all Croatian regions and coupled with the nearest regional and county hospitals in the organizational network.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…According to this and other investigations 15 , there is a respectable access to tertiary hospitals for urgent cardiac patients in Croatia. tertiary hospitals are distributed across all Croatian regions and coupled with the nearest regional and county hospitals in the organizational network.…”
Section: Discussionmentioning
confidence: 62%
“…each of the eleven PCI centers in Croatia with 24/7 work schedule had a catchment population of 384,000 inhabitants, approaching the number of at least 600 primary PCIs per million inhabitants. On the contrary, we found that only 380-390 non-St-segment elevation myocardial infarction (nStemI) patients per million inhabitants received PCI in the first 72 hours 15 . Croatia has achieved a decreasing mortality trend in coronary heart disease, as well as in the overall cardiovascular pathology in the past ten years (53% vs. 47%).…”
Section: Introductionmentioning
confidence: 89%